Memahami Pentingnya Manfaat Microsoft Onenote pada Pembelajaran di Sekolah atau Kampus - Dwi Erlanda Anggara; Sy Haura Munawwarah; Indah Lestari; Ridha Tri Handayani (Universitas Muhammadiyah Enrekang, 2022)
There has been a tremendous growth of information communication technology (ICT) worldwide in recent years. A major shift is also occurring in the way users integrate technology into their personal lives. This research was conducted on the basis of a desire to investigate the benefits of Microsoft OneNote in the business world. The Quantitative Method is the method used by the author, this method is used to describe Microsoft OneNote through information gathering which is carried out through document studies such as articles, e-books, and papers. Microsoft OneNote is an Office application that functions like a notepad, where you can write, draw, insert objects, doodle, display screenshots, leave comments, and share them with coworkers. Different from Microsoft Word, in OneNote you can write and put anything in any place you like. Much like when doodle on paper, in OneNote you are also free to place note elements.